EFEK SENAM LANSIA TERHADAP PENYAKIT ATRITIS PADA LANSIA DI PUSKESMAS TAMALATE MAKASSAR - Jumrana Jumrana; Asmaul Husnah (Lembaga Pengembangan Kinerja Dosen, 2022)
Based on the initial data taken at the Tamalate Makassar Health Center in 2019, the population of 84 people from the last 3 months visited. The purpose of this study was to find out the effects of elderly gymnastics on atritis disease in the elderly in Tamalate Makassar Health Center. The research design used is qualitative experiment method, using quasi experiment approach with one group pretest and posstest design with population of 84 people, Sample 30 people, obtained by using Purposive Sampling technique, Statistical test using paired sample T test. Statistical test results using paired sample T test obtained sig value 2-tailed (0.000) < value (0.05), means Ho rejected and Ha received. Conclusion thus there is a significant relationship of the effects of elderly gymnastics on atritis disease in the elderly in Tamalate Makassar Health Center.